Dynamic imaging of cell wall polysaccharides by metabolic click‐mediated labeling of pectins in living elongating cells. (6th March 2022) - Ropitaux, Marc; Hays, Quentin; Baron, Aurélie; Fourmois, Laura; Boulogne, Isabelle; Vauzeilles, Boris; Lerouge, Patrice; Mollet, Jean‐Claude; Lehner, Arnaud
SUMMARY: Protein tracking in living plant cells has become routine with the emergence of reporter genes encoding fluorescent tags. Unfortunately, this imaging strategy is not applicable to glycans because they are not directly encoded by the genome. Indeed, complex glycans result from sequential additions and/or removals of monosaccharides by the glycosyltransferases and glycosidases of the cell's biosynthetic machinery. Currently, the imaging of cell wall polymers mainly relies on the use of antibodies or dyes that exhibit variable specificities. However, as immunolocalization typically requires sample fixation, it does not provide access to the dynamics of living cells. The development of click chemistry in plant cell wall biology offers an alternative for live‐cell labeling. It consists of the incorporation of a carbohydrate containing a bio‐orthogonal chemical reporter into the target polysaccharide using the endogenous biosynthetic machinery of the cell. Once synthesized and deposited in the cell wall, the polysaccharide containing the analog monosaccharide is covalently coupled to an exogenous fluorescent probe. Here, we developed a metabolic click labeling approach which allows the imaging of cell wall polysaccharides in living and elongating cells without affecting cell viability. The protocol was established using the pollen tube, a useful model to follow cell wall dynamics due to its fast and tip‐polarized growth, but was also successfully tested on Arabidopsis root cells and root hairs. This method offers the possibility of imaging metabolically incorporated sugars of viable and elongating cells, allowing the study of the long‐term dynamics of labeled extracellular polysaccharides. Significance Statement: This paper reports a protocol for the metabolic‐click mediated dynamic imaging of a pollen tube, a rapidly elongating plant cell. This method results in the fluorescent labelling of cell wall polysaccharides in living cells, allowing the study of their long‐term dynamics.